Relational Transilience in the Garden: Plant–Human Encounters in More-than-Human Life Narratives - Alexander Vera (Open Cultural Studies)
Whereas many indigenous and non-western cultures see plants and humans as connected, western worldviews tend to disregard plants as material commodities. Plant non-thinking of this kind is increasingly being challenged in response to the environmental threats arising from human exceptionalism. This essay investigates garden narratives as a form of more-than-human life writing which depicts plant–human relations as mutually transformative and reciprocal. I argue that garden narratives pioneer such a rethinking as a win-win scenario. The positive developments garden writers document are consistent with a concept put forward in environmental psychology: transilience. Making reference to five recent western garden narratives I show how plant encounters can help us move towards an emerging environmental culture which emphasises more-than-human embeddedness and embraces symbiotic over competitive relations.